(untitled) (Filološke pripombe, 2021)
Childhood, as a unique period of development of each individual, in which all life experiences are experienced for the first time, leaves a deep mark on the child’s psyche and because of this it is in the center of interest of many children’s writers. In particular, this article is devoted to the complex processes of growing-up and maturation as seen through the perspective of authors James Matthew Barry and Jadranka Vladova in their children’s novels Peter Pan and “The Mirror Behind the Mirror. Through the main characters Peter Pan and Maya (whose attitude towards growth is quite a contrast) the development of the child’s soul is presented, its character formation and some of the possible problems that arise during that process. Peter Pan is a symbol for a boy who refuses to grow up because he is satisfied with his own freedom and independence, but like any other child, he longs at the same time for sincere motherly love and care. In contrast to him, in Vladova’s novel the girl Maja wants to grow up too fast in order to get rid of loneliness, as well as to gain the right of choice and a sense of security that is found in adults. Common to both characters is the premature abandonment of parental protection and care, before their maturity (with Petar because of the desire for freedom, while with Maja because of the unavailability of the parents). This circumstance of events leads to problems in the development of both characters. The boy Peter Pan never reaches emotional and cognitive maturity, while the girl Maya falls into dangerous delusions and fantasies from which she frees herself through socializing with her peers, when she realizes that she should not rush into life and preoccupy herself with the difficult problems of adults. Through the events described in these novels, the authors actually achieve their goal of warning about some of the possible problems that arise in the process of growing up and subtly influencing the shaping of the characters of fragile children, their habits and ways of behaving and thinking.